Paradigms of Education in the Art of Acting - CODREANU, Cătălin (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
Embedded in interculturality and transculturality, this paper focuses on the actor’s training, on facing, understanding and assimilating the theater lessons of the Far East, especially those of the Nō theater, based on the constructive encounters with them by practicing the Tadashi Suzuki (b. 1939) method, Japanese martial arts, researching Zen philosophy and the writings of Zeami Motokiyo (1363-1443). This article points out the similarity between certain paradigms of the Western theatricality with those of the Far Eastern one (holism, body-mind, here and now, flow, imaginary) as well as their fusion with other paradigms due to the interdisciplinary transfer existing between martial arts (aikidō and iaidō), Japanese culture, and the art of acting (shin-waza-tai, shoshin, ichigo ichie). The way in which fixed forms relate to imagination (kata), specific to both Far Eastern theater and martial arts (aikidō and iaidō), is also very important. This research highlights the essential nature of the fixed form for the impulses of imagination and creative freedom.